트리티케일 파종시기 및 수확시기가 사일리지 사료가치와 기능성 성분에 미치는 영향 - 김지숙; Jisuk Kim; 라경윤; Kyungyoon Ra; 김율호; Yul-ho Kim; 박명렬; Myoung Ryoul Park (Korean journal of crop science, 2022)
Triticale forage has the highest yield of all winter forage crops, including rye, and a cold tolerance within an average low temperature of -10°C in January. Therefore, this study analyzed the effects of sowing and harvesting times on the feed value and functional components of triticale to optimize the use and supply of triticale as livestock fee Room temperature' can vary widely with climate, season, and time of day. In order to clearly state the conditions of the study in a manner that facilitates replication by other researchers, please consider using an approximate temperature range instead. Seeds of the triticale ‘Joseong’ were sown during the fall of 2021 (October 20th) and spring of 2022 (March 7th). The triticale was harvested at the following growth stages: seedling stage, booting stage, heading stage, 10 days after heading, and 20 days after heading. The moisture content of each harvested triticale was adjusted to approximately 60%, and the triticale was fermented for silage for 40 days at ambient temperature under anaerobic conditions. We measured the pH and organic acid content of each silage to determine the feed value and functional component. The lactic acid content of the triticale silage harvested at the seedling stage sown in both fall and spring (1.61%, 1.63%) was the highest among all the silages. The octacosanol content in the silages of both fall-sown and spring-sown triticale harvested at the seedling stage (0.38, 0.27 mg/ml) was the highest. Overall, the results revealed that harvesting time had a greater impact on the feed value and functional components of triticale silage than sowing time.